P. falciparum rosetting mediated by a parasite-variant erythrocyte membrane protein and complement-receptor 1. - Rowe, J; Moulds, J; Newbold, C; Miller, L (1997)
The factors determining disease severity in malaria are complex and include host polymorphisms, acquired immunity and parasite virulence. Studies in Africa have shown that severe malaria is associated with the ability of erythrocytes infected with the parasite Plasmodium falciparum to bind uninfected erythrocytes and form rosettes. The molecular basis of resetting is not well understood, although a group of low-molecular-mass proteins called rosettins have been described as potential parasite ligands. Infected erythrocytes also bind to endothelial cells, and this interaction is mediated by the parasite-derived variant erythrocyte membrane protein PfEMP1, which is encoded by the var gene family. Here we report that the parasite ligand for rosetting in a P. falciparum clone is PfEMP1, encoded by a specific var gene. We also report that complement-receptor 1 (CR1) on erythrocytes plays a role in the formation of rosettes and that erythrocytes with a common African CR1 polymorphism (S1(a-)) have reduced adhesion to the domain of PfEMP1 that binds normal erythrocytes. Thus we describe a new adhesive function for PfEMP1 and raise the possibility that CR1 polymorphisms in Africans that influence the interaction between erythrocytes and PfEMP1 may protect against severe malaria.